2020
DOI: 10.3389/fdgth.2020.576945
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Synthetic Electronic Health Record Data and Deep Learning to Improve Timing of High-Risk Heart Failure Surgical Intervention by Predicting Proximity to Catastrophic Decompensation

Abstract: Objective: Although many clinical metrics are associated with proximity to decompensation in heart failure (HF), none are individually accurate enough to risk-stratify HF patients on a patient-by-patient basis. The dire consequences of this inaccuracy in risk stratification have profoundly lowered the clinical threshold for application of high-risk surgical intervention, such as ventricular assist device placement. Machine learning can detect non-intuitive classifier patterns that allow for innovative combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In fact, we are already starting to see published (observational) health research using synthetic derivatives only. 40 While we found that there were very little differences between the real and synthetic data on the bivariate comparisons, one may hypothesise that this was influenced by the fact that the effect sizes were small. However, that was not the case for the multivariate models where the effect sizes were larger and the differences between the real and synthetic datasets remained small.…”
Section: Limitationsmentioning
confidence: 69%
See 3 more Smart Citations
“…In fact, we are already starting to see published (observational) health research using synthetic derivatives only. 40 While we found that there were very little differences between the real and synthetic data on the bivariate comparisons, one may hypothesise that this was influenced by the fact that the effect sizes were small. However, that was not the case for the multivariate models where the effect sizes were larger and the differences between the real and synthetic datasets remained small.…”
Section: Limitationsmentioning
confidence: 69%
“…In addition to offering more options for addressing privacy concerns, sharing synthetic versions of clinical trial datasets can potentially alleviate the need for obtaining ethics board reviews for such analysis projects, 40 simplifying and accelerating research studies.…”
Section: Relevance and Application Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we utilized electronic health record (EHR) data from a large academic liver transplant center. Our institution partnered with MDClone [ 18 , 19 ] (Beer Sheva, Israel) for the data storage and retrieval. MDClone platform is a data engine by storing EHR medical events in a time order for each patient.…”
Section: Methodsmentioning
confidence: 99%